GRAMMAR TEACHING STRATEGIES OF ESL EDUCATORS IN MALAYSIAN HIGHER EDUCATION - Abdul Rahman, Ayuni Madarina (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This research explores how English as a Second Language (ESL) educators employed the strategies to teach grammar in classrooms within Malaysian higher education institutions, particularly the ways they address the challenges. A qualitative design was employed where the data was collected through semi-structured interviews with five ESL educators across various Peninsular Malaysia. The findings revealed four key strategies: peer collaboration for resource sharing, ongoing professional development to adapt to evolving pedagogies, reliance on standardized reference materials for instructional consistency, and modification of assessment rubrics to capture implicit grammar learning. While these strategies reflect educators’ commitment to learner-centred instruction, institutional constraints, particularly exam-oriented curricula, limit their wider application. The study contributes to theory, practice, and policy by aligning educator strategies with Communicative Language Teaching, Task-Based Language Teaching and Sociocultural Theory. Practically, it offers insights for curriculum reform, targeted teacher training, and more flexible assessment practices. Future research should integrate student perspectives and classroom observations to validate findings and extend insights across broader Malaysian and regional ESL contexts.